A corpus study of the diachronic development of Chinese patent terminologies. Issue 1 (2nd January 2020) - Tsai, Yvonne
ABSTRACT: Corpus-based approaches to the study of language and the compilation of a corpus are increasing at an unprecedented rate in recent years. The majority of the corpus was compiled from newspaper articles or by combining literatures with non-literatures. Corpus in specialized fields is mostly related to legal language, with very few monolingual or parallel corpora in the technical field, not to mention diachronic corpus. The building of a corpus and corpus-based studies facilitates terminologists, translators, researchers, and teachers in specialized English a basis in their analysis and interpretation of specialized terminologies. Diachronic corpus helps us understand the development of language and explores the changes and uses of specialized language in a specific field, in order to provide terminologists and translators a reference when defining specific terms. This study compiles a diachronic corpus of Chinese patent claims and abstracts to explore the linguistic features of the Chinese patent terminologies, the development, and variations of patent terminologies. With the diachronic corpus of Chinese patent claims, the development of patent terminologies can be analyzed. The patent is a strong indicator of the economic power of a country. The authentic material collected in the patent corpus provides representative research data, which, in turn, increases our understanding of the use of terminologies of patents.